Anger Damns the Innocent. (August 2021) - DeCelles, Katherine A.; Adams, Gabrielle S.; Howe, Holly S.; John, Leslie K.
False accusations of wrongdoing are common and can have grave consequences. In six studies, we document a worrisome paradox in perceivers' subjective judgments of a suspect's guilt. Specifically, we found that people (including online panelists, n = 4, 983, and working professionals such as fraud investigators and auditors, n = 136) use suspects' angry responses to accusations as cues of guilt. However, we found that such anger is an invalid cue of guilt and is instead a valid cue of innocence; accused individuals (university students, n = 230) and online panelists ( n = 401) were angrier when they are falsely relative to accurately accused. Moreover, we found that individuals who remain silent are perceived to be at least as guilty as those who angrily deny an accusation.